Inversion Method of Logging Data by Array Temperature Difference Flow Tool for Horizontal Wells in Tight Oil Reservoirs - CHEN Qiang; CHEN Meng; YUAN Chao; CHEN Tao; CHEN Wenhui; LIU Guoquan (Cejing jishu)
Due to the extremely poor physical properties of tight reservoirs, the yield of single well is generally low. Accurately monitoring and evaluating the dynamics of oil-water phase flow in horizontal wells, and obtaining the oil and water production of each layer is the basis for understanding the dynamics of the production zones, evaluating the effectiveness of reservoir renovation, optimizing and adjusting the development scheme. At the present stage, production profile logging tools, e.g. MAPS and FSI, using the array turbine flowmeters to monitor the multiphase flow, which are terribly affected by the mechanical structure, instrument rotation, and casing significant monitoring errors. In the paper, based on the monitoring data of the array temperature difference flowmeter for horizontal wells in tight reservoirs, relationships between the temperature difference responses and the flow velocity, water holdup are built based on the simulation experiments. Then the interpolation algorithm is introduced to calculate the local position fluid velocity of the six flowmeter probes. A new method for calculating the fluid velocity by taking into account of the rotation and distribution of the array probes is also established. Applications of actual production wells showed that the established model in the manuscript can achieve an accurate quantitative evaluation of oil-water production dynamics in lower flow rate horizontal wells. The error of the full flow rate layer compared with the production of the wellhead is less than 15.0%, which provides feasible technical support for the monitoring and evaluation of production dynamics of horizontal wells in tight oil reservoirs.